Sex differences in the renin-angiotensin-aldosterone system and its roles in hypertension, cardiovascular, and kidney diseases - Nwia, Sarah M.; Leite, Ana Paula O.; Li, Xiao Chun; Zhuo, Jia Long (Frontiers in Cardiovascular Medicine, 2023)
Cardiovascular disease is a pathology that exhibits well-researched biological sex differences, making it possible for physicians to tailor preventative and therapeutic approaches for various diseases. Hypertension, which is defined as blood pressure greater than 130/80 mmHg, is the primary risk factor for developing coronary artery disease, stroke, and renal failure. Approximately 48% of American men and 43% of American women suffer from hypertension. Epidemiological data suggests that during reproductive years, women have much lower rates of hypertension than men. However, this protective effect disappears after the onset of menopause. Treatment-resistant hypertension affects approximately 10.3 million US adults and is unable to be controlled even after implementing ≥3 antihypertensives with complementary mechanisms. This indicates that other mechanisms responsible for modulating blood pressure are still unclear. Understanding the differences in genetic and hormonal mechanisms that lead to hypertension would allow for sex-specific treatment and an opportunity to improve patient outcomes. Therefore, this invited review will review and discuss recent advances in studying the sex-specific physiological mechanisms that affect the renin-angiotensin system and contribute to blood pressure control. It will also discuss research on sex differences in hypertension management, treatment, and outcomes.